Aerodynamic Mitigation of Wind Uplift on Low-Rise Building Roof Using Large-Scale Testing - Azzi, Ziad; Habte, Filmon; Elawady, Amal; Gan Chowdhury, Arindam; Moravej, Mohammadtaghi (Frontiers in Built Environment, 2020)
During strong wind events such as hurricanes and thunderstorms, building roofs are subjected to high wind uplift forces (suctions), which often lead to severe roofing component damage and possibly, water intrusion. It is therefore crucial to accurately estimate peak suctions (negative pressures) on roofs for design purposes and to develop mitigation devices to reduce wind uplift and possible damage. Past research suggests that mitigation devices, in various forms and configurations, can significantly reduce wind effects on buildings’ roofs. Perforated parapets have been shown by many researchers to be one of the most effective and low-cost mitigation devices for reducing roof suction. However, such devices contain perforations of critical functionality that may be Reynolds number Re dependent. Therefore, it is essential to study their functionality and possible Re dependency in wind tunnel testing. This paper focuses on investigation of Reynolds number Re similitude aspects of porous devices and large-scale model testing of discontinuous porous parapets to estimate their roof uplift reduction efficacy that would be representative of the prototype (full-scale) conditions. Large scale (1:8) experiments were implemented at the 12-Fan Wall of Wind Experimental Facility (WOW) at Florida International University (FIU) to achieve adequate local Reynolds number Re to ensure realistic results. In this study, a relatively smaller ratio of parapet height to roof height has been considered as compared to previous studies. The paper delineates the step-by-step design of the parapets based on kinematic similitude requirements cited in the literature. The goal was to achieve a discontinuous porous parapet design that provides similar uplift reduction efficacy as compared to those reported in the literature, but with lower height and smaller length to ensure cost-effectiveness, ease of installation, and architectural aesthetics of the retrofitted building. The effects of perforated parapets on both individual tap and area-averaged pressure coefficients were explored. The results indicated a maximum of 45% reduction in individual tap peak pressure coefficients at the corner roof and a 40% reduction in area-averaged peak pressure coefficients. The study showed that low-height ratio perforated parapets could be as effective as those reported in the literature with higher height ratios.